2016
DOI: 10.1039/c6cc00268d
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the grain size of organic halide perovskites by sulfonate-carbon nanotube incorporation in high performance perovskite solar cells

Abstract: The grain size of perovskites was enhanced and the grain boundary was filled with sulfonate carbon nanotubes (s-CNTs) during the CH3NH3PbI3 perovskite precursor solution spin-coating process with the incorporation of s-CNTs. The performance of s-CNT incorporated perovskite solar cells remarkably increased from 10.3% to 15.1% (best) compared with pristine CNT incorporated perovskite solar cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(69 citation statements)
references
References 35 publications
(35 reference statements)
2
65
0
2
Order By: Relevance
“…Although it has been reported that grain boundaries have not to adversely affect solar cell characteristics in CIGS and halide perovskite solar cell, nevertheless, an effective strategy for efficient carrier management in a CZTS layer is to make the grain size not too small. Generally, grain boundary control is a key concern for polycrystalline thin‐film solar cells . A light absorber consisting of small grains can degrade the device performance due to the vertical current flow through the multiple grain boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been reported that grain boundaries have not to adversely affect solar cell characteristics in CIGS and halide perovskite solar cell, nevertheless, an effective strategy for efficient carrier management in a CZTS layer is to make the grain size not too small. Generally, grain boundary control is a key concern for polycrystalline thin‐film solar cells . A light absorber consisting of small grains can degrade the device performance due to the vertical current flow through the multiple grain boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…130 For example, fullerene derivatives, such as PCBM, were used as hole transport layers and integrative component to reduce hysteresis and charge recombination. [131][132][133][134] Furthermore, SWCNTs and MWCNTs were used as dopants for HTMs, such as Spiro-MeOTAD, 135,136 as integrative component into the perovskite layer, 137,138 and as hole extraction layer. 139,140 As such, charge recombination losses were reduced and hole collection efficiencies were increased.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a broad range of physical and chemical characteristics of CNT, possibly endowed by chemical modification and heteroatom doping, could provide open opportunities for the perovskite‐based hybrid structures and interfacial engineering 13b,14. Recently, CNT has been utilized as reinforcing components in the perovskite layers for optoelectronic applications, particularly motivated from their high charge carrier mobility . Nonetheless, the strong tendency for aggregation and intrinsic chemical inertness of pristine CNT makes it challenging to achieve a desired synergistic integration 15d,16.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, CNT has been utilized as reinforcing components in the perovskite layers for optoelectronic applications, particularly motivated from their high charge carrier mobility . Nonetheless, the strong tendency for aggregation and intrinsic chemical inertness of pristine CNT makes it challenging to achieve a desired synergistic integration 15d,16. Moreover, potential interaction mechanism between perovskite crystal structure and graphene plane is still unclear, which is crucial for the desirable hybrid structures.…”
Section: Introductionmentioning
confidence: 99%